2021
DOI: 10.1002/acm2.13322
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiological evaluation considering setup error on single‐isocenter irradiation in stereotactic radiosurgery

Abstract: Purpose: We calculated the dosimetric indices and estimated the tumor control probability (TCP) considering six degree-of-freedom (6DoF) patient setup errors in stereotactic radiosurgery (SRS) using a single-isocenter technique.Methods: We used simulated spherical gross tumor volumes (GTVs) with diameters of 1.0 cm (GTV 1), 2.0 cm (GTV 2), and 3.0 cm (GTV 3), and the distance (d) between the target center and isocenter was set to 0, 5, and 10 cm. We created the dose distribution by convolving the blur componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…3, 4). As was also shown by the results of previous studies, we observed that the physical dose reduction rate of the GTV increased due to a smaller GTV size, an increased distance from the isocenter, and an increased error in the 6DoF setup [11,12,14]. Some studies reported an increase in the PTV margin because the physical dose of the GTV decreases with increasing distance from the isocenter [13,40].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…3, 4). As was also shown by the results of previous studies, we observed that the physical dose reduction rate of the GTV increased due to a smaller GTV size, an increased distance from the isocenter, and an increased error in the 6DoF setup [11,12,14]. Some studies reported an increase in the PTV margin because the physical dose of the GTV decreases with increasing distance from the isocenter [13,40].…”
Section: Discussionsupporting
confidence: 82%
“…2021b software (MathWorks, Natick, MA, USA) was used. The coordinates (unit: cm) of the GTVs were set so that the distance (d) from the center of the GTV to the set at the origin of the coordinate axes was 0-10 cm [14,27]. First, a uniform dose distribution was created by adding a margin to each GTV (Fig.…”
Section: Phantom Design and Dose Distribution Generationmentioning
confidence: 99%
See 3 more Smart Citations